2017
DOI: 10.1016/j.je.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of abdominal obesity among Chinese adults in 2011

Abstract: BackgroundThe prevalence of abdominal obesity is increasing dramatically worldwide. This study aimed to estimate the current prevalence of abdominal obesity from the 2011 China Health and Nutrition Survey (CHNS) and compare the data with other countries.MethodsWaist circumference (WC) of 12,326 Chinese adults (aged 20 years or older) from the 2011 CHNS were analyzed by age group and region. Abdominal obesity was defined as a WC ≥90 cm for men and WC ≥80 cm for women based on World Health Organization (WHO) rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 34 publications
5
39
1
3
Order By: Relevance
“…is high. Compared to other studies among women, prevalence of CO in this study as defined by WC is higher than 53.8% found in Nigeria [17], 47.1% among Saudi women [18], 51.7% national prevalence of Chinese women [8], 57.7% among Lome women in Togo [19]. The prevalence in this study is comparable to the finding of an earlier study among Nairobi women in Kibera that found CO prevalence at 67.5% [20].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…is high. Compared to other studies among women, prevalence of CO in this study as defined by WC is higher than 53.8% found in Nigeria [17], 47.1% among Saudi women [18], 51.7% national prevalence of Chinese women [8], 57.7% among Lome women in Togo [19]. The prevalence in this study is comparable to the finding of an earlier study among Nairobi women in Kibera that found CO prevalence at 67.5% [20].…”
Section: Discussionsupporting
confidence: 54%
“…Central obesity poses a threat to cardio-metabolic health of individuals independently of overall obesity [7]. Rising trends in central obesity have been found in populations of different countries [8]. A study among Syrian women found central obesity as defined by WC was higher than BMI derived obesity [9].…”
Section: Introductionmentioning
confidence: 99%
“…Although great efforts have been made to control the weight of the population in China, the prevalence of obesity continues to increase, especially in the rural areas 2. According to the data obtained in the China Health and Nutrition Survey (CHNS) in 2011, the prevalence of abdominal obesity was 44.0% in rural China 3. A recent study also showed that the age-standardised prevalence of abdominal obesity was 43.71% in rural Chinese adults 4.…”
Section: Introductionmentioning
confidence: 99%
“…Du and collaborators [23] suggested that the diet seems to be more important than physical activity to explain the association between education and anthropometric markers of intra-abdominal adipose tissue. The education factor seems to influence the risk of obesity mainly for being associated to the consumption of industrialized food, rich in fat and sugar, nevertheless, in countries in dietary transition, including Brazil, receiving constant inflow of food products, such as processed food with low nutritional values [24].…”
Section: Discussionmentioning
confidence: 99%